RELIGIOUSLY GLOWING: BLENDING RELIGIOUS EXPRESSION IN SKINCARE ADS - Raushanfikr, Alia Nisa Alexandrina; Kusumawati, Feby Diah; Rachmanda, Fransiska Dina; Kasanah, Fatimah Nur (Universitas Gunadarma, 2024)
In Indonesia, many skincare product advertisements carry religious themes in them. This research focuses on religious expressions used in Wardah, Safi and Kahf skincare product advertisements. The three skincare product advertisements combine religious expressions in the form of concepts, symbols and stories. This research also examines the meaning of religious expressions in Wardah, Safi and Kahf advertisements. The theory used in this research is the theory of the relationship between religion and advertising by Stefanie Knauss (2016). This research aims to prove the function of religious expressions in Wardah, Safi and Kahf skincare product advertisements with descriptive qualitative method through observation and analysis of the three advertisements. From the results of the research, the writer found that religious expressions in Wardah, Safi and Kahf skincare product advertisements to attract consumers, especially for Muslim consumers in Indonesia. This research can be used as a reference base and foundation for studies that focus on analyzing the meaning contained in religious expressions in skincare product advertisements.